The Study Role of Contribution of Vitamin D, Cholecalciferol, To the Immunological Response Following a COVID-19 Infection - Mohammad Sharhan, Batoul Abdul Husseen; Fadil, Taqwa Salih Abdulsahib; Mohammad, Zahraa Radi Harijah; Ali Ashour, Nabaa Thamer Mohammad (Journal of Science in Medicine and Life, 2024)
There is a worldwide health crisis as a result of the COVID-19 epidemic. Regarding this virus's defensive properties, not much is known. Therefore, there is an urgent need for preventative treatments that might lessen the severity, duration, and risk of infection. The review examined vitamin D's possible Its symptoms are in respiratory infections, such as Covid-19. In addition, credit score As of May 20, 2020, this research has shown a relationship between vitamin D levels and Covid-19 cases and deaths in 20 European countries. There is a significantly poor association (p = 0.033) between mean and vitamin D levels and COVID-19 cases per million people in developing countries. This did not happen with Covid-19 deaths in these countries, although there was a strong relationship. Research has indicated a relationship between the Corona virus and deaths and vitamin D levels; however, when confounding variables were taken into account, no association was identified in other research.